The Xiangya Ocular Tumor Bank: A Disease-Specific Biobank for Advancing Translational Research Into Ocular Tumors - Gao, Zhaolin; Tan, Jia; Wang, Sha; Yu, Haiyang; Zhou, Ziyu; Zhang, Yun; Zhou, Mushi; Xia, Xiaobo; Yao, Fei; Huang, Jufang (Frontiers in Medicine, 2022)
The pathogenesis and etiology of various ocular tumors remain unknown, limiting the development of diagnosis and treatment of ocular tumors. Tissue samples of patients are the most significant source to elucidate ocular tumors' molecular mechanisms. Herein, we built an ocular tumor biobank to collect human samples, aiming to provide valuable resources for translational and molecular biological studies. The biobank holds biological materials and clinical data from patients who underwent surgery in Department of Ophthalmology of Xiangya Hospital from December 1, 2018 to January 31, 2020. Blood and tissue samples and associated clinical data were systematically collected. Operating procedures for collection, transportation, processing and conservation of ocular tumor samples have been developed. All the specimens were collected from 92 donors covering 21 types of eye tumors and several undiagnosed eye diseases. A total of 846 samples are preserved in the ocular tumor biobank, including 356 blood samples (42.1%), 324 plasma samples (38.3%) and 166 tissue samples (19.6%). In the clinical data analysis of all the donors diagnosed with ocular tumor, we identified the prevalence of malignant ocular tumors was associated with variables of age, gender, tumors' location and size and presenting complaints of lump and proptosis. The factors predictive of malignant ocular tumors, including gender (B = 1.599; P = 0.025) and the symptom of proptosis (B = -2.534; P = 0.001). On the whole, our biobank can provide various biological and clinical resources, contributing to accelerating progress in the pathogenesis and clinical research and promoting precision medicine.